Military-patriotic education in Russia: How the next generation is being brought into line with the regime - Margarete Klein; Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2025)
Since 2022, the Russian leadership has significantly expanded its activities in the area of military-patriotic education for children and young people. New compulsory measures and voluntary programmes have been introduced. Their apparent diversity notwithstanding, the Kremlin has strict control over these new measures and programmes. Its goal is to educate the next generation in accordance with the Russian leadership's line, recruit loyal young people for the regime and the armed forces, and identify at an early stage those who might become critics of the regime. The new measures cover a growing number of children and young people and now extend even to kindergartens. Those affected respond with enthusiasm, indifference or opportunism. Overt resistance is evident only in isolated cases owing to the heavy pressure to conform and the repressive nature of the regime.
Keywords: 320; military-patriotic education in Russia; Kremlin; pressure to conform; repressive regime; Vladimir Putin; Sergei Shoigu